Government expenditure, inflation rate and economic growth in Nigeria (1981-2013): A vector autoregressive approach - Sanmi Olubokun; Ebiwonjumi Ayooluwade; F. O. Fawehinmi (Romanian Journal of Fiscal Policy (RJFP), 2016)
The study investigated the impacts of government expenditure and inflation rate on economic growth in Nigeria from 1981 to 2013. The data for the study were generated from the Central Bank of Nigeria (CBN) statistical bulletin and was analyzed using the Vector Auto Regressive (VAR) modeling approach. The variance decomposition shows that high level of government expenditure and inflation contributed significantly to shocks in the real gross domestic product. The central focus of the study is that fluctuation in output growth over the years is a true reflection of the level of government expenditure as well as the inflationary level in Nigeria. There is therefore, an urgent need for policy makers to formulate policies that will enhance real gross domestic product and consequently generate sustainable economic growth and development in the country.
Keywords: H50; E31; O40; C59; 330; Vector Autoregressive Model; Real Gross Domestic Product; Government Expenditure; Inflation Rate; Exchange Rate